Bush encroachment effects on above-ground biomass, species, composition, plant diversity and selected soil properties in a semi-arid savanna grassland - Mogashoa, Regina Etla (My University, 2020)
Bush encroachment is a major problem in arid and semi-arid savannas characterized by a grass layer interspersed with a shrub stratum. Land cover change as a result of rapid proliferation of woody species in previously open rangelands alters herbaceous species and impacts soil properties. So far, little is known about the threshold at which woody plant density and cover affects herbaceous cover and the underlying mechanisms driving bush encroachment in arid and semi-arid rangelands are still debated. The objectives of this dissertation were to (1) to assess woody species composition and structure along an encroachment gradient and to explore the relationship between woody vegetation and herbaceous vegetation. (2) To determine the effect of increasing tree density and cover on grass species richness, diversity, evenness and selected soil nutrients in a bush encroached rangeland. In order to address these objectives, a semi-arid rangeland was demarcated into three encroachment gradients spanning from open to intermediate and intensive. Within each encroachment gradient six plots of 10 m x 10 m were randomly selected, whereby woody and herbaceous vegetation were assessed and soil properties determined. A discernible increase in woody species diversity and evenness was found along the transition from open to intensive bush encroached rangeland. Leguminous woody species Vachellia spp. and Dichrostachys cinerea were dominant along the bush encroachment gradient. Tree height was found to be positively correlated with long crown diameter (LCD) and short crown diameter (SCD). Furthermore, increasing tree density resulted in a 53% decline in grass species richness (GR). A decline in GR mirrored an increase in the composition of the decreaser species Panicum maximum (90%). Increasing woody plant density and cover also increased macro-nutrients; total carbon, nitrogen, phosphorus, exchangeable calcium and magnesium by 21%-159% in the shallow rangeland soils. Such quantitative information will assist rangeland managers to better understand the effects of varying bush encroachment intensities on herbaceous species composition, richness and soil properties in semi-arid savanna rangelands.
Thesis (M.Sc. Agriculture (Pasture Science)) -- University of Limpopo, 2020
Keywords: Bush encroachment; Species richness; Diversity; Composition; Soil properties; Semi-arid; Savanna; Rangelands; Grasslands -- South Africa; Rangelands; Arid regions